From Jemdet Nasr origins to an early Muslim town in the wetlands: second preliminary report on excavations at Kobeba (Dhi Qar governorate), southern Iraq - Simpson, St John (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2023)
In 2022, targeted excavations were carried out as part of a study season at the site of Kobeba, near the town of al-Rifa’i, in Dhi Qar governorate, southern Iraq. The results were very successful and clarified a number of outstanding questions over the dating and phasing. One sounding has confirmed a deep sequence of Jemdet Nasr occupation with evidence for pottery production and a fragment of a jar with part of a carefully incised pictographic inscription. A second sounding has gone below the latest two levels of 8th century early Islamic occupation to reach a third level with more substantial architecture datable to the 7th century, and a Sasanian level below that. This sequence is now one of the most important for these periods from Iraq and there are clear changes in the pottery which will help future surveys in this region. Finally, a test trench excavated last year in the fields beyond the site was expanded into a larger area, and the results proved that there is an archaeological layer contemporary with the latest period of occupation at Kobeba at a depth of 1.60 m below plain level and resting directly on top of an ancient marsh deposit: this proves that at this period Kobeba was in a wetland environment very different to the present situation.